Inhibitory effects of some medicinal plant extracts on the growth of Ascosphaera apis - P. Chantawannakul (2018)
Ascosphaera apis is a fungal pathogen causing Chalkbrood disease in honey bee larvae. Chalkbrood is most frequent during damp conditions. Infected larvae turn chalky white color, become hard, and then turn black. It can be regarded as "the most widespread infectious disease" in Thailand and this has led to economic loss in apiculture. A. apis strains were isolated on Potato Dextrose Agar (PDA) from the dead honey bee larvae, collected from infected hives in Northern Thailand. The fungal strains were identified as A. apis by their morphology in comparison with the A. apis IFO9831. We aim to find an alternative approach by using medicinal plants in combating and controlling the disease. Studies on the effect of crude medicinal plant extracts, therefore, have been carried out. Dried powdered plants (Allium sativum Linn, Eugenia caryophyllum Bullock&Harrison, Piper betel, Curcuma longa Linn, Illicium verum Hook, Cinnamomum cassia, Rhinacanthus nasutus Kurz, Azadirachta siamensis, Acorus calamus Linn., and Stemona tuberosa Lour) were extracted in seven different solvents by incubating for 48 hours. The aqueous extracts in suitable solvent of E. caryophyllum, P. betel, I. verum, C. cassia, A. calamus, and gave inhibitory effect when tested with Thai isolates of Ascosphaera apis. Various concentrations (0.25-10%) of the extract of the five chosen plants were experimented. Cinnamomum cassia and Piper betel (1.5-3.5% (w/v)) gave best inhibitory effects on the fungal growth. These results suggest that either cinnamon or betel piper extract, alone or in combination, could well be used for Chalkbrood control in the future. © ISHS 2005.